Heterogeneity of metastatic gastric cancer: solitary non-regional lymph node metastasis and solitary lung metastasis showed better survival outcomes than other metastatic patterns - Xiaoyi Luan; Xue Han; Zerong Wang; Lulu Zhao; Xiaojie Zhang; Wanqing Wang; Penghui Niu; Danjun Wang; Dongbing Zhao; Mingwei Zhu; Yingtai Chen (BMC Cancer)
Abstract Background Although metastatic gastric cancer has remarkably poor prognosis, a small group of patients achieved relatively favorable survival outcomes due to the disease’s variable biological behavior. The study aimed to investigate the impact of metastatic patterns on survival outcomes of metastatic gastric cancer patients. Methods Patients with distant metastatic (M1) gastric cancer in the China National Cancer Center between January 1999 to December 2019 were retrospectively reviewed. Univariate and multivariate cox regression analyses tested the relationship between metastatic patterns and survival. Results A total of 2,042 patients with definitive information on metastatic organs were included in the study. Liver (772 [37.9%]), peritoneum (765 [37.6%]), and non-regional lymph node (692 [34.0%]) were the most three common metastasis organs for metastatic gastric cancer patients in our study. The median survival time of patients with metastatic gastric cancer was 15.4 months. For patients with solitary non-regional lymph node metastasis, the 2-year and 5-year overall survival (OS) rates were notably high at 48.12 and 24.55%, respectively. Patients with solitary lung metastasis demonstrated similarly favorable survival outcomes, with 2-year and 5-year OS rates reaching 46.45 and 16.02%. However, patients with multi-organ metastases faced the poorest prognosis among those with metastatic gastric cancer, with 26.98% of them surviving more than 2 years, and only 8.35% surviving more than 5 years. In multivariate cox regression analyses, solitary non-regional lymph node metastasis [multiple organs Ref; hazard ratio (HR) 0.636, 95% CI 0.507–0.798, P < 0.001] and solitary lung metastasis (multiple organs Ref; HR 0.535, 95% CI 0.336–0.852, P = 0.008) were independent beneficial prognostic factors in metastatic gastric cancer patients. Conclusions Gastric cancer patients with solitary non-regional lymph node metastasis and solitary lung metastasis showed better survival outcomes than other metastatic gastric cancer patients. Sub-classifying metastatic gastric cancer based on metastatic organs is recommended, which could assist in forecasting survival outcomes and facilitating individualized treatment.